The effect of load on the fretting wear behavior of TC4 alloy treated by SMAT in artificial seawater - Liu, Zhenlin; Xu, Feng; Luan, Xiaoxiao; Yu, Sujuan; Guo, Baoli; Zhang, Xiaofeng; Xin, Long (Frontiers in Materials, 2024)
The TC4 alloy has become an ideal material for marine engineering due to its excellent corrosion resistance, high specific strength and light weight in seawater. However, components made from TC4 alloys often come into contact with parts such as propellers and turbine engine blades, leading to severe fretting wear during operation and significantly reducing their service life. In this study, the untreated TC4 alloy samples were used as the control group, and the samples after 240 min of surface mechanical attrition treatment (SMAT) were selected to investigate the fretting wear behavior under different load conditions in artificial seawater environment. The results show that the friction coefficient of TC4 alloy remains relatively unaffected by load variations, both before and after SMAT treatment. With the increase of load, the fretting regime gradually changed from gross slip to partial slip, and the wear depth, volume and wear rate increased. Under the same load, the wear volume of TC4 alloy after SMAT treatment is significantly reduced, indicating that its wear performance has been improved.